Soft Skills in Counseling Children with Special Needs - Tita Rosita; Juntika Nurihsan (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2025)
The purpose of this study is to examine the soft skills needed to counsel children with special needs in schools. This study uses a qualitative method with literature review. The soft skills examined in this study include the skills needed to implement counseling for various children with special needs, which must be trained by undergraduate students majoring in guidance and counseling and psychology. Based on the results of the study, in order to train soft skills for counseling children with special needs, there needs to be an integration of counseling practicum courses in collaboration with several disability communities and schools that have children with special needs, so that the counseling practicum process can be more factual with the needs in inclusive schools. The soft skills that need to be trained in counseling children with special needs are the ability to empathize, the ability to solve problems with diverse student disabilities, and effective communication.